Actividades lúdicas para el rendimiento escolar en la asignatura de la matemática en los estudiantes de cuarto año de EGB paralelo “A” de la unidad educativa Juan Benigno Vela, cantón Echeandía provincia Bolívar, periodo académico mayo – septiembre 2022 - Encarnación Arreaga, Yomara Lisseth (2022)
The present investigative study was carried out in the Juan Benigno Vela Educational Unit, corresponding to the INEC urban area belonging to the city of Echeandía, Bolívar province. The research arises with the problem of school performance in the subject of mathematics in fourth year EGB students, which includes the lack of knowledge on the part of the teachers in charge of that area, for which the variables of the subject were inquired of research obtaining a scientific contribution from authors who have made their contributions regarding the subject of study. On the other hand, the methodology used in the research project allowed us to develop the research process satisfactorily, in such a way that it gave real results with the help of techniques and materials that facilitated the collection of information to carry out an analysis on it and thus arrive to clear conclusions that will allow us a viable solution with the application of ludic activities in the strengthening of the academic performance of the mathematics subject. It should be noted that all this investigative process led to the development of a methodological guide with recreational activities that will contribute favorably to the strengthening of mathematical performance and learning in fourth-year EGB children and in such a way that adequate and quality education can be provided. in which children develop their skills and abilities in an enthusiastic way.